2018
DOI: 10.1002/cam4.1826
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin 2 confers primary resistance to sorafenib by simultaneously activating AKT and AMPK in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the malignancy derived from normal hepatocytes with increasing incidence and extremely poor prognosis worldwide. The only approved first‐line systematic treatment agent for HCC, sorafenib, is capable to effectively improve advanced HCC patients’ survival. However, it is gradually recognized that the therapeutic response to sorafenib could be drastically diminished after short‐term treatment, defined as primary resistance. The present study is aimed to explore the role of stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 62 publications
1
30
2
Order By: Relevance
“…On the other hand, Sestrins may block oxidative damage-associated chemotherapy by reducing ROS (Budanov and Karin, 2008;Hagenbuchner et al, 2012). Sestrins were upregulated upon drug treatments in various type of pre-and mature-tumors as cell survival mechanism: head and neck cancers (Won et al, 2019), non-alcoholic steatohepatitis (Huang et al, 2020), HCC (Dai et al, 2018), osteosarcoma (Yen et al, 2018), acute pancreatitis (Norberg et al, 2018), colitis (Ro et al, 2016), bladder cancer (Hua et al, 2018), and prostate cancer (Fu et al, 2018;Shan et al, 2019). The distinctive roles of Sestrins as tumor suppressor or oncogene in the early or late stages of cancers need further investigation (Sanchez-Alvarez et al, 2019).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…On the other hand, Sestrins may block oxidative damage-associated chemotherapy by reducing ROS (Budanov and Karin, 2008;Hagenbuchner et al, 2012). Sestrins were upregulated upon drug treatments in various type of pre-and mature-tumors as cell survival mechanism: head and neck cancers (Won et al, 2019), non-alcoholic steatohepatitis (Huang et al, 2020), HCC (Dai et al, 2018), osteosarcoma (Yen et al, 2018), acute pancreatitis (Norberg et al, 2018), colitis (Ro et al, 2016), bladder cancer (Hua et al, 2018), and prostate cancer (Fu et al, 2018;Shan et al, 2019). The distinctive roles of Sestrins as tumor suppressor or oncogene in the early or late stages of cancers need further investigation (Sanchez-Alvarez et al, 2019).…”
Section: Sestrins In Nutrient Stress-sensing and Metabolic Dysfunctionmentioning
confidence: 99%
“…Sestrins are induced by a variety of stresses such as DNA damage, hypoxia, and metabolic changes ( Dai et al, 2018 ). Previous studies have shown that most forms of cancer are associated with the down-regulation of Sestrin2 ( Chen et al, 2016 ; Seo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…SESN3 can also be regulated by serum and cytokines/growth factors [55]. While information in this regard is still limited, a number of reports directly link dysregulated SESN expression levels with specific types of cancer cells [56,57,58], suggesting a potential for classifying and inferring oxidative stress resilience phenotypes.…”
Section: Sestrins At the Crossroads Of Ros Oxidative Stress And Amentioning
confidence: 99%